Sosialisasi Pedagogi Olahraga melalui Permainan Edukatif Balance Board Sensory di SLB Negeri Pembina Palembang Sumatera Selatan - Septaliza, Dewi; Martinus,; Endrawan, I Bagus; Muslimin,; Melianty, Selvi; Taroreh, Bangkit Seandi; Gustianto, Fahrulrozi (TAAWUN, 2023)
The purpose of community service socialization of sports pedagogy through sensory balance board educational games at SLB Negeri Pembina Palembang is one of the efforts to increase understanding of sports pedagogy in the community. Community service activities are carried out in three stages, namely 1) planning, 2) implementation and 3) evaluation. Data collection through observation while data analysis techniques using quantitative analysis. Subjects amounted to 17 people. The results of community service show that there is an increase in understanding by 100% (17 people). Another thing that was revealed was that students showed a desire to learn, were active during the game, were happy and cheerful. Sensory balance board educational games are an alternative choice of sports pedagogy games that can be utilized by the community.